The failed century of the child : governing America's young in the twentieth century - Sealander, Judith (Cambridge University Press, 2003)
Between 1900 and 2000 an unprecedented American effort to use state regulation to guarantee health, opportunity, and security to the country's children failed to reach its goals. The achievements envisioned were enormously ambitious and reflected entrenched but self-contradictory values and Americans' inconsistent expectations of government. As such, a 'failed' century deserves a mixture of rebuke and cautious admiration. Starting with the young, American public policy transformed individuals into strings of measurable characteristics. People became statistics, and if society could just get the measurements right, social policy said, progress would be possible. But children proved hard to quantify. Policies based on optimistic faith in the powers of applied scientific truth revealed perils implicit in acceptance of poorly understood social science paradigms. Definitions changed, as psychology or sociological or statistical theory changed, and good intentions foundered, as experts fiercely challenged each other's conclusions and public policies sought to respond.